The productivity paradox of corporate taxation: A nonlinear tale of growth and constraints - Hang T. T. Nguyen (Arbeitskreis Quantitative Steuerlehre (arqus), 2026)
This paper investigates the relationship between corporate income tax rates (CITR) and firm-level productivity growth using AMADEUS data of 304,410 observations from 79,842 European firms from 2006 to 2019. The results imply a robust non-linear relationship: higher CITRs are positively associated with productivity growth for high-productivity firms near the technological frontier and negatively associated with the productivity catch-up of less productive firms. Heterogeneity tests suggest a stronger productivity response to tax rate changes of small and medium-sized enterprises (SMEs) and domestic firms, while I do not find a significant productivity response to tax rate changes for large and multinational firms. The main findings are robust across various productivity estimation methods and model specifications and challenge the conventional view that higher business tax rates have a linear and negative effect on productivity growth. The paper contributes to the ongoing debate about the role of corporate taxation in shaping economic competitiveness and long-term growth.
Keywords: 330; Körperschaftsteuer; Steuertarif; Produktivitätsentwicklung; Betriebsgröße; Nichtlineare Regression; Schätzung; Europa